Une guerre sans fin ? L’utopie, la famille, et le monde post 11-Septembre dans Doctor Who de Russel T. Davies - Alec Charles (ReS Futurae)
This essay explores the ideological positioning of Russell T. Davies’s reinvention of the classic British TV series Doctor Who. Davies’s program has announced in its themes, settings, and allusions an unusually direct engagement with contemporary politics : specifically, the repercussions of the Al-Qaeda strikes of September 11, 2001. Like American television’s Heroes and Battlestar Galactica, the new Doctor Who argues against the totalizing strategies advanced by both sides in the war on terror, denouncing violent modes of pseudo-Utopian fundamentalism in favor of pluralist and personal solutions to global problems. Yet it has also remained aware of its own protagonists’ potential to succumb to such forms of fanaticism. Exploring in detail the reimagined Doctor Who’s first four seasons (2005-2008), the essay shows how the series investigates, juxtaposes, and perhaps eventually reconciles two concepts central to its narrative : Utopia and family.